IMPLEMENTASI PROGRAM KAMPUNG IKLIM OLEH DINAS LINGKUNGAN HIDUP KOTA DUMAI TAHUN 2019-2021 - Siregar, Linda Yusnita; Harira, Zulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Climate Village Program or Proklim is an activity that combines climate change adaptation and mitigation efforts at the site level with the involvement and active role of the community and supporting parties, namely the government and regional governments as well as entrepreneurs, universities and non-governmental institutions. This research aims to describe the implementation of Sustainable Development Goals SDGs in the Climate Village Program by the Dumai City Environmental Service. The focus of this research is only in 2021. The Climate Village Program in Dumai City has been socialized since 2018 on the basis of Presidential Regulation Number 59 of 2017 concerning the Implementation of SDGs and the Regulation of the Director General of Climate Change Control, Ministry of Environment and Forestry of the Republic of Indonesia Number P. 1PPISETKUM. 122017 concerning Guidelines for Implementing the Climate Village Program and strengthened by the instruction of the Governor of Riau Number 01INT-HK2017 concerning guidance, assistance and strengthening of the location of the Riau Province Climate Village Program. This research uses a qualitative descriptive method where data is collected through interviews with informants. This research focuses on three sub-districts, namely Laksamana, Bukit Datuk, and Tanjung Palas. The theory used in this research is Donald Van Meter and Carl Van Horn's Implementation Theory which consists of four variables, namely Environmental Conditions, Inter-Organizational Relations, Resources, and Character of the Implementing Institution. The results of the research show that the implementation of the Sustainable Development Program in the Climate Village Program in Dumai City in these three sub-districts has gone well, from the four variables, namely different environmental conditions that create characteristics between sub-districts, relationships between organizations that run well, supported by community participation. Adequate resources due to the existence of farmer groups and youth organizations as concrete steps for the program. As well as the character of the implementing institution which is responsible and carries out the program in accordance with the roadmap that was agreed upon before implementing the program. Keywords: Implementation, Climate Village Program